2020
DOI: 10.1111/jocn.15140
|View full text |Cite
|
Sign up to set email alerts
|

“Sage on the stage or guide on the side”—Undergraduate nursing students’ experiences and expectations of bioscience tutors in a blended learning curriculum: A qualitative study

Abstract: Aims and objectives This study sought to explore undergraduate nursing students’ perceptions of the role and value of their bioscience tutors in a blended learning curriculum. Background Blended learning approaches typically have reduced face‐to‐face contact with tutors—particularly in bioscience subjects which nursing students have traditionally found difficult, and the move to more web‐based learning resources may compound this difficulty. Design Qualitative descriptive study. Methods This qualitative study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Teaching bioscience to nursing students in large classes can be challenging due to students’ lack of confidence (Bakon et al., 2016), their struggles with off‐campus preparations and the resulting variation in their level of preparedness, and their preference for a teacher‐centred approach (Bingen et al, 2019; Koch et al., 2020; O’Flaherty & Phillips, 2015). Our findings indicated that struggling students could benefit from more in‐class lectures to build their foundation of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching bioscience to nursing students in large classes can be challenging due to students’ lack of confidence (Bakon et al., 2016), their struggles with off‐campus preparations and the resulting variation in their level of preparedness, and their preference for a teacher‐centred approach (Bingen et al, 2019; Koch et al., 2020; O’Flaherty & Phillips, 2015). Our findings indicated that struggling students could benefit from more in‐class lectures to build their foundation of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding about the curriculum content in blended learning has been developed in previous studies such as curriculum content in the teaching-learning process considered important facts, principles, and concepts that can be knowledge, skills, attitude, and values that students expose to learn (Lunenburg, 2011a , b ). Koch et al ( 2020 ) identified the significance of the blended learning curriculum of bioscience and provided students' insights into what they reflected as good and inadequate approaches to learning. Yu and Du ( 2019 ) explained the delivery of the curriculum content through tremendous advancements in technology that have become central points in modern higher education for both face-to-face learning and online learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, participants preferred to also have a face-to-face portion to resolve their unanswered questions and allow them to practice new skills. The desire for face-to-face encounters has also been highlighted in clinical training programs [29,35]. These findings around interest in both modalities reinforce the value of blended approaches [36] in which participants experience the flexibility of digital self-training and engagement and interactivity in face-to-face sessions.…”
Section: Discussionmentioning
confidence: 76%